A molecular clock for autoionization decay - Medisauskas, Lukas; Bello, Roger Y.; Palacios, Alicia; Gonzalez-Castrillo, Alberto; Morales, Felipe; Plimak, Lev; Smirnova, Olga; Martin, Fernando; Ivanov, Misha Yu (Journal of Physics B: Atomic, Molecular and Optical Physics, 2017)
The ultrafast decay of highly excited electronic states is resolved with a molecular clock technique, using the vibrational motion associated to the ionic bound states as a time-reference. We demonstrate the validity of the method in the context of autoionization of the hydrogen molecule, where nearly exact full dimensional ab-initio calculations are available. The vibrationally resolved photoionization spectrum provides a time-energy mapping of the autoionization process into the bound states that is used to fully reconstruct the decay in time. A resolution of a fraction of the vibrational period is achieved. Since no assumptions are made on the underlying coupled electron-nuclear dynamics, the reconstruction procedure can be applied to describe the general problem of the decay of highly excited states in other molecular targets.
CRIS-Team Scopus Importer:2023-04-20
Keywords: attosecond dynamics; autoionization; coupled electronic-nuclear dynamics; molecular clock